Housing space and ICT usage: A cross sectional case study in the Netherlands. (July 2021) - Qin, Xiao; Zhen, Feng; Zhang, Shanqi
Abstract: Information and communication technology (ICT) has reshaped the definition of the home by increasing flexibility in selecting residential locations, which can provide safe and comfortable environments for work, communication and leisure. However, few studies have comprehensively focused on the relationship between housing space and ICT usage. The present study collects survey data in the Netherlands and uses a zero-inflated negative binomial regression to analyse the relationship. Results show that (1) houses located in highly or strongly urbanised area are positively related with the duration of teleservices and general ICT usage; (2) detached, semi-detached and town houses are positively related with the duration of telecommuting; (3) flats are positively related with the adoption of telecommuting, the duration of teleservices, and the adoption and duration of teleleisure; and (4) the number of rooms is positively related with the adoption of telecommuting and the duration of general ICT usage but negatively related with the duration of teleleisure. Finally, the relationships between ICT usage with different housing space attributes and travel are discussed to support the policy making of transportation, environment and housing spatial layout. Highlights: Houses in highly urbanized area are positively related with the duration of teleservices and general ICT usage. Detached, semi-detached and town houses are positively related with the duration of telecommuting. Flats are positively related with the adoption of telecommuting and teleleisure, and the duration of teleservices and teleleisure. The number of rooms is positively related with the adoption of telecommuting and the duration of general ICT usage. The number of rooms has negative associations with the duration of teleleisure.